Venture capital exits in domestic and cross-border investments - Espenlaub, Susanne; Khurshed, Arif; Mohamed, Abdulkadir (Journal of Banking & Finance, 2015)
We compare and contrast the performance of cross-border and domestic venture capital (VC) investments in terms of the time it takes VC backers to exit portfolio companies through initial public offering (IPO), trade sale (M&A), or other routes. Initial analysis suggests that cross-border investments are exited more quickly than domestic investments, and this difference is driven by the cross-border investments in North America. We explore whether the difference between domestic and cross-border exits can be explained by regional variations in economic/market activity and legal systems. We find it is important to allow for the impact of these macro variables on the time to VC exit to vary across regions. This is crucial not just to capture the full impact of the macro factors, but also to explain the differences in time to exit between domestic and cross-border investments.